(untitled) (American Journal of Public Diplomacy and International Studies (2993-2157), 2024)
The place of national folklore in the application of magical means in Uzbek and English literary fairy tales can be examined through a comparative analysis of how cultural traditions, beliefs, and mythologies influence the portrayal and use of magic in these narratives. Here are some theoretical perspectives on this topic, along with examples from Uzbek and English literary fairy tales: